2021
DOI: 10.3389/fpubh.2021.751828
|View full text |Cite
|
Sign up to set email alerts
|

Gender Modifies the Association of Cognition With Age-Related Hearing Impairment in the Health and Retirement Study

Abstract: Introduction: Despite growing recognition of hearing loss as a risk factor for late life cognitive disorders, sex and gender analysis of this association has been limited. Elucidating this is one means to advocate for holistic medicine by considering the psychosocial attributes of people. With a composite Gender Score (GS), we aimed to assess this among aging participants (50+) from the 2016 Health and Retirement Study (HRS) cohort.Methods: The GS was derived from gender-related variables in HRS by factor anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 63 publications
(84 reference statements)
1
6
0
Order By: Relevance
“…The incidence rates reported in this study were comparable with previous studies. 37 38 39 40 41 42 43 44 45 For instance, the incidence rate of cognitive impairment was 52.6 cases/1000 person-years in a 5-year follow-up study of Aboriginal Australians aged over 60 years, 46 which is similar to our result (64.6 cases/1000 person-years). The observed sex- and age-disparities in incidence rates also corresponded to prior knowledge.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The incidence rates reported in this study were comparable with previous studies. 37 38 39 40 41 42 43 44 45 For instance, the incidence rate of cognitive impairment was 52.6 cases/1000 person-years in a 5-year follow-up study of Aboriginal Australians aged over 60 years, 46 which is similar to our result (64.6 cases/1000 person-years). The observed sex- and age-disparities in incidence rates also corresponded to prior knowledge.…”
Section: Discussionsupporting
confidence: 90%
“…16 Using claim data, Jin and colleagues also conducted a network analysis for diseases with strong associations. 18 We assessed the associations between ARFIs, based on previous studies that have discovered unidirectional 44 45 51 52 or bidirectional relations between sensory impairments, such as vision and hearing, depression, and cognitive impairment. 44 45 51 53 54 For example, a meta-analysis of longitudinal studies indicated that visual impairment was associated with a 66% higher risk of cognitive impairment, and that cognitive impairment was also associated with the incidence of visual impairment.…”
Section: Discussionmentioning
confidence: 99%
“…Respondents indicated whether or not they heard each tone. Consistent with previous work, we defined hearing less than all 6 tones in the best ear as possible hearing loss 5,6 …”
Section: Methodsmentioning
confidence: 92%
“…Consistent with previous work, we defined hearing less than all 6 tones in the best ear as possible hearing loss. 5,6 Logistic regression was used to characterize the association of suboptimal perception of patient-centered care by hearing status. Covariates included: age, sex, race/ethnicity, marital status, educational attainment, insurance status, has usual source of care, and number of self-reported chronic comorbidities.…”
Section: Methodsmentioning
confidence: 99%
“… 15 Using claim data, Jin and colleagues also conducted a network analysis for diseases with strong associations. 33 We assessed the associations between ARFIs, based on previous studies that have discovered unidirectional 36 , 37 , 38 or bidirectional relations between sensory impairments, such as vision and hearing, depression, and cognitive impairment. 36 , 37 , 38 , 39 , 40 For example, a meta-analysis of longitudinal studies indicated that visual impairment was associated with a 66% higher risk of cognitive impairment, and that cognitive impairment was also associated with the incidence of visual impairment.…”
Section: Discussionmentioning
confidence: 99%